Intron and Its Splicing Mechanism and Their Connection with Human Disease - Dosay-Akbulut, Mine (Bangladesh Journal of Medical Science, 2016)
In the maturation mechanism of a messenger RNA, splicing play an important role with removing the noncoding introns and ligating the coding exons. Alternative splicing (AS) gives an extra difficulty to this mechanism and to the regulation of gene expression. The possible disturbing in the alternative RNA splicing mechanism can be a reason to several diseases like cancers and neurodegenerative disorders. Intronless genes (IGs) are seen in almost 3% of the human genome. Functionality of IGs has an important role in signal transduction genes and related regulatory proteins. This diversity can be reason to IG-associated diseases, especially neuropathies, developmental disorders, and cancer. The retroelements can be seen in almost half of the human genome. The known informations indicate that insertion of retroelement into exons and introns of genes promote different types of genetic disease, including cancer. The retroelement connected mutagenesis cause to fifty different types of human disease. The molecular informations and bioinformatic analyses can be used to explain the connection with splicing mutations and genetic mechanisms of several different human disease and understanding of this mechanism play an important role in the formation of treatment programme against to these diseases. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.307-312